2008
DOI: 10.1258/ijsa.2007.007172
|View full text |Cite
|
Sign up to set email alerts
|

Preferred options for receiving sexual health screening results: a population and patient survey

Abstract: Current genitourinary medicine patients (202) and potential future patients (542) completed a questionnaire-based survey to determine their preference for obtaining test results, their acceptability of including a named infection on contact slips and to report expectations about the acceptable length of an appointment. Overall, most respondents (78% [n = 582]) felt it unacceptable to be only contacted if their results were positive ('no news is good news'). In the clinic, a majority preferred a contact slip to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Telephone notification of test results was the first choice of most men in our study, which is consistent with other studies on receiving sexual health screening results (Brown, Copas, Stephenson, Gilleran, & Ross, 2008). Men's acceptance of alternative test result notification methods, such as e-mail and text messaging, is promising.…”
Section: Discussionsupporting
confidence: 91%
“…Telephone notification of test results was the first choice of most men in our study, which is consistent with other studies on receiving sexual health screening results (Brown, Copas, Stephenson, Gilleran, & Ross, 2008). Men's acceptance of alternative test result notification methods, such as e-mail and text messaging, is promising.…”
Section: Discussionsupporting
confidence: 91%
“…This supports the recent paper which revealed that patients prefer the 'human touch', i.e., prefer telephone and face-to-face contact rather than the newer technologies. 4 However, in our clinic very few patients chose to return for their results (0.2%), which may be a reflection of our particular clinic. We serve a mixed urban and rural population and travel distances/travel times can be considerable.…”
Section: Discussionmentioning
confidence: 95%
“…prefer telephone and face-to-face contact rather than the newer technologies. 4 For reasons of improved patient choice and improved clinical governance, we needed to change from NNIGN and so we asked our service users for their preferences for obtaining results. At the same time we also designed a new clinic results service to deliver normal/negative results to patients.…”
Section: Introductionmentioning
confidence: 99%
“…20 Our results support the introduction of text messaging, especially as an alternative to the 'no-news-is-good-news' policy at GUM clinics that was consistently disliked in our sample and that is comparable to previous findings. 21 Strengths and weaknesses of the study A possible limitation of this study is that all the participants in our focus groups were current or previous users of STI testing services, and therefore, their preferences may differ from those with no experience of testing or those who choose not to test. We cannot comment on the distribution of testing services that participants had direct experience of as we wanted to limit the amount of personal data we collected about informants.…”
Section: Relation To Wider Literaturementioning
confidence: 99%